Testing a Model of Depression Among Thai Adolescents - Vatanasin D. (2017)
Problem: This predictive correlational study was designed to test a comprehensive model of depression for Thai adolescents. Methods: This sample included 800 high school students in Chiang Mai, Thailand. Data were collected using self-reported measures of depression, negative automatic thoughts, effective social problem solving, ineffective social problem solving, rumination, parental care, parental overprotection, and negative life events. Findings: Structural equation modeling revealed that negative automatic thoughts, effective and ineffective social problem solving mediated the effects of rumination, negative life events, and parental care and overprotection on adolescent depression. Conclusion: These findings provide new knowledge about identified factors and the mechanisms of their influence on depression among Thai adolescents, which are appropriate for targeting preventive interventions. © 2012 Wiley Periodicals, Inc.